Sistema de Evaluación de Impacto Ambiental para obras de aprovechamiento hidráulico para las categorías Ecología e Interés Humano, en el periodo 2019 – 2020. - Chuquitarco Caiza, Karina Gissela (2020)
In the actuality, the serious shortage of water resources proposes great challenges in diferent parts of the world due to its overexploitation, for that reason its management must be carried out from the perspective of a scarse good, applying methods which can reduce environmental impacts.This research purpose was to apply the BC environmental impact assessment methodology in hydraulic projects for ecological and human interest categories. The BC methodology was applied to the Coca Codo Sinclair (CCS) hydraulic exploitation work, which is a government work for hydroelectric generation and electricity transmission to the National Interconnected System (SNI), with a design flow of 285 m3/s, caught from the Quijos River at its confluence with the Salado River, being part of the hydrographic basin of the Napo River (Amazon slope)which is the largest in the country. CCS environmental studies have not provided for the integrated management of water resources with local participants, even to face problems of water stress (drinking water, sanitation or floods), or extreme current and future climate variability, which affects human security in the Amazon foothills. For this reason, the research evaluates the impacts in Ecological and Human Interest categories, using the baseline data from EsIA EFFICACITAS and ENTRIX. Through prediction and identification of possible impacts, significant values were obtained for the phase without and with the project, through a graphic representation of the environmental quality (CA), mentioning the possible effects that would generate adverse environmental changes. As evaluation result was determined that 9 of the 18 parameters of the Ecological category shows a percentage lower than 10%, generating a low tonality alert, while the remaining 9 parameters shows a higher tonality alert signal exceeding 10%. In Human Interest category, its evaluation concludes that 13 of 19 parameters show an alert of a lower tonality when it is below 30%, and the remaining 6 when exceeding 30% indicate an alert signal of a higher tonality. In conclusion, in Ecology category, some conditions in all of this area were changed, due to the extension of the agricultural frontier and the different activities developed by CCS; On the other hand, the Human Interest category detected two positive impacts related to employment opportunities and social interactions, which in turn, they influence the weakening of culture and deterioration of historical value. The use of the proposed methodology is suggested, to obtain exact results by calculating the overall environmental impact of the Project.